Spinal muscular atrophy with progressive myoclonic epilepsy: A case report from China with new ASAH1 variants - Xiaojing Yin; Jinghe Shi; Daoqi Mei; Jianmei Guo; Tingting Ma; Yuna Gao; Li Wang; Jie Deng (Heliyon)
We report a case of a Chinese girl who presented with multiple seizure types of epilepsy, followed by motor and intellectual regression, vision impairment, and cerebral and cerebellar atrophy. She carries an unreported compound heterozygous variant of the ASAH1 gene and is diagnosed with spinal muscular atrophy associated with progressive myoclonic epilepsy (SMA-PME), a disorder in which ceramide accumulation in lysosomes due to a decrease in acid ceramidase activity. This case suggests attention to this rare class of deceases involving both the central and peripheral nervous systems.